Anticancer Ribosomally Synthesized and Post-Translationally Modified Peptides from Plants: Structures, Therapeutic Potential, and Future Directions - Hyeon-Jeong Hwang; Youngsang Nam; Chanhee Jang; Eun La Kim; Eun Seo Jang; Yeo Jin Lee; Seoung Rak Lee (Current Issues in Molecular Biology)
Cancer remains a significant medical challenge, necessitating the discovery of novel therapeutic agents. Ribosomally synthesized and post-translationally modified peptides (RiPPs) from plants have emerged as a promising source of anticancer compounds, offering unique structural diversity and potent biological activity. This review identifies and discusses cytotoxic RiPPs across various plant families, focusing on their absolute chemical structures and reported cytotoxic activities against cancer cell lines. Notably, plant-derived RiPPs such as rubipodanin A and mallotumides A–C demonstrated low nanomolar IC50 values against multiple cancer cell types, highlighting their therapeutic potential. By integrating traditional ethnobotanical knowledge with modern genomic and bioinformatic approaches, this study underscores the importance of plant RiPPs as a resource for developing innovative cancer treatments. These findings pave the way for further exploration of plant RiPPs, emphasizing their role in addressing the ongoing challenges in oncology and enhancing the repertoire of effective anticancer therapies.